Middle-level management capability in Central Kalimantan Regional Police - Santosa, Budi; Thalib, Prawitra; Suhariadi, Fendy; Trisliatanto, Dimas Agung (Technium Social Sciences Journal, 2024)
Middle-level managerial capabilities in the Central Kalimantan Regional Police could also be referred to as relevant role capabilities for members who hold managerial positions at each level of the Resort Police and Sector Police. The Middle Officer's capabilities consisted of the quality of impact and influence ability, achievement drive, cooperation, analytical thinking, initiative, developing others, self-confidence, understanding others, direction/assertiveness, information seeking, team leadership, conceptual thinking, organizational awareness and fostering relationships, and specific knowledge capabilities. This study aimed to analyze middle-level management capability in Central Kalimantan Regional Police. Police as a modern organization in general also expect to have human resources who were proactive and show initiative, had responsible for their own professional development, and committed to high quality performance standards. Police in middle-level management capabilities were qualities and actions that the main characteristics of professional people at the level of Middle Officers. The conclusion of this study explained that the development of middle-level management capabilities in the human capital personnel of the Central Kalimantan Regional Police, especially at the Resort Police level, was one of the main focuses for balancing external developments that adapted to internal conditions within the police institution. external developments which were bureaucratic reforms carried out and seeing these challenges, while internal conditions in the form of the institution's ability to map personnel and direct human capital capabilities to be able to win the competition and demands for quality police performance also require serious efforts to make it happen because the performance The current police bureaucracy was suspected to have not shown optimal performance.